2020
DOI: 10.1016/j.pss.2019.104815
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of cometary particles collected by COSIMA: Assessing the differences between microscopic and macroscopic scales

Abstract: The COSIMA mass spectrometer on-board Rosetta was equipped with an optical microscope, Cosiscope, which identified several 10,000 cometary particles collected on targets exposed during the orbital phase around the nucleus of comet 67P Churyumov-Gerasimenko. The median value of reflectance factors evaluated from Cosiscope images for large collected particles (~10.5% (Langevin et al., 2017), lies above the range of reflectance observed by the OSIRIS camera at a similar wavelength (5-7%, (Fornasier et al., 2015),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…This agrees with the results from Rosetta’s in situ sampling, in particular microscopic imaging of grains by the COSIMA (Langevin et al. 2020 ; Kimura et al. 2020 ) and MIDAS instruments (Mannel et al.…”
Section: Scientific Contextsupporting
confidence: 90%
“…This agrees with the results from Rosetta’s in situ sampling, in particular microscopic imaging of grains by the COSIMA (Langevin et al. 2020 ; Kimura et al. 2020 ) and MIDAS instruments (Mannel et al.…”
Section: Scientific Contextsupporting
confidence: 90%
“…Additionally, experimental simulations under different conditions (including microgravity) suggest the presence of fluffy aggregates with comparable amounts of minerals and organics (Levasseur-Regourd et al 2015). This agrees with the results from Rosetta's in situ sampling, in particular microscopic imaging of grains by the COSIMA (Langevin et al 2020;Kimura et al 2020) and MIDAS instruments (Mannel et al 2019).…”
Section: Dust Comasupporting
confidence: 80%
“…At 1.3 AU, the bolometric albedo of comet C/2013 US 10 (Catalina) is likely measuring the reflectance properties of the refractory particles because ice grains have very short lifetimes at this heliocentric distance (Beer et al 2006;Protopapa et al 2018). Reflectance of individual refractory particles from the coma of comet 67P/Churyumov-Gerasimenko as measured by Rosetta COSIMA/Cosicope are from 3% to 22% at 650 nm (Langevin et al 2017(Langevin et al , 2020, which spans the range of bolometric albedos measured for comet comae.…”
Section: Dust Bolometric Albedomentioning
confidence: 91%
“…Stardust samples demonstrate that aerodynamic sorting in aggregate formation occurred for particles of olivine compared to FeS, which are denser than olivine (Wozniakiewicz et al 2013(Wozniakiewicz et al , 2012. The Rosetta mission's imaging studies showed that comet 67P/Churyumov-Gerasimenko's particles are hierarchical aggregates of hundreds of microns to mm-size with components that are submicron to tens of micron in size (Langevin et al 2020;Güttler et al 2019;Hornung et al 2016) Stardust samples and Rosetta particle studies are commensurate with the idea that aggregate particle components of submicron to tens of micron of size may be favored over larger solid particles in their outward movement to the disk regimes of comet-nuclei formation.…”
Section: Comet Crystalline Silicates and Disk Transportmentioning
confidence: 99%